Molecular detection of Rotavirus type A in diarrheic calves of Mid-Euphrates governorates Iraq: Qassim Haleem Kshash1 and Hamed Abbas Hassan2 - Kshash, Qassim Haleem (The Iraqi Journal of Veterinary Medicine, 2018)
Four hundred fecal samples from diarrheic calves of both sexes (1-60 days old) from four Iraqi Mid-Euphrates governorates (Babylon, Al-Najaf, Karbala and Al-Qadissiyiah) were collected to investigate rotavirus type A infection by using Real-Time Polymerase Chain Reaction technique. The results showed that infection rates were (14%), while the high rate (20%) was found in age of (1-30 days), however non-significant values were related to animal gender. Moreover, a high infection was recorded at January (29.5%) and the rotraviral infection was recorded in four provinces but the higher was in Babylon (23%). The clinical examination of infected calves showed voluminous watery diarrhea, profound weakness and mild depression; the body temperature, respiration and heart rates were decreased significantly and appetite was changeable towards loss or anorectic.